Odpowiedzi

2010-02-09T18:22:38+01:00
3a+6
-4x+y
5x+y
7t+14s +7
8x+8y+16x
3x+12+6x
6a+8b+2c
7x+14y+21z
8x+12y+20z
2010-02-09T18:23:25+01:00
3(a-2)= 3a-6
b) -4(x+y)=-4x-4y
c) -5(-x+y)=5x-5y
d) (t-2s-1)7=7t-14st-6
e) 8(x+y-2x)=8x+8y-6x=2x+8y
f) 3(x+4-2x)=3x+4-6x+3x+4
g) 2(3a-4b+c)=6a-8b+2c
h) 7(x+2y-3z)=7x+14y-21z
i)4(2x-3y-5z)= 8x-12y-20z
Najlepsza Odpowiedź!
2010-02-09T18:26:52+01:00
A)3(a-2)=3a-6
b) -4(x+y)=-4x-4y
c) -5(-x+y)=5x-5y
d) (t-2s-1)7=7t-14s-7
e) 8(x+y-2x)=8x+8y-16x=-8x+8y
f) 3(x+4-2x)=3x+12-6x=-3x+12
g) 2(3a-4b+c)=6a-8b+2c
h) 7(x+2y-3z)=7x+14y-21z
i)4(2x-3y-5z)=8x-12y-20z